-3(-7+m)=

Simple and best practice solution for -3(-7+m)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(-7+m)= equation:


Simplifying
-3(-7 + m) = 0
(-7 * -3 + m * -3) = 0
(21 + -3m) = 0

Solving
21 + -3m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-21' to each side of the equation.
21 + -21 + -3m = 0 + -21

Combine like terms: 21 + -21 = 0
0 + -3m = 0 + -21
-3m = 0 + -21

Combine like terms: 0 + -21 = -21
-3m = -21

Divide each side by '-3'.
m = 7

Simplifying
m = 7

See similar equations:

| 3x-5=137 | | 17x=5y+1 | | -4a^2-45a-50=0 | | x+48=x | | 8v+13=3v+18 | | 3x+40+10=180 | | 6(2x+4)=3(8+4x) | | x^-3/2=0 | | 6x-5y+3=-27 | | 9cot^2x+1=4 | | X^3-4x^2-14x-60=0 | | 3x+10+40=360 | | 9=3p+6 | | 8b-13b= | | 9cot^2x=4 | | x+4+2x=137 | | 11s+12t=93 | | P=275/12i1714 | | 7w+4=5w-10 | | 6(2Y+2)-9=3 | | 1-7x=6x-129 | | 2(T-2)+9=-9 | | 5(3x-1)=-10x+20 | | 6/(2/3) | | 9(5n+4)= | | 5p+6q=54 | | 3/5y-6/5=4 | | 2p+3q=24 | | 3x(x+1)-x(3x+1)=x-7 | | -2(5a+5)= | | 10k+8-7k= | | 8=3x-5/2 |

Equations solver categories